Enhanced in vivo anti-tumor efficacy of whole tumor lysate in combination with whole tumor cell-specific polyclonal antibody - Ilnaz Rahimmanesh; Yasaman Esmaili; Elham Ghafouri; Seyed Hossein Hejazi; Hossein Khanahmad (Wolters Kluwer Medknow Publications, 2023)
Background and purpose: Despite the widespread utilization of cancer vaccines with specified antigens, the use of whole tumor cell lysates in tumor immunotherapy would be a very promising approach that can overcome several significant obstacles in vaccine production. Whole tumor cells provide a broad source of tumor-associated antigens and can activate cytotoxic T lymphocytes and CD4+ T helper cells concurrently. On the other hand, as an effective immunotherapy strategy, recent investigations have shown that the multi-targeting of tumor cells with polyclonal antibodies, which are also more effective than monoclonal antibodies at mediating effector functions for target elimination, might minimize the escape variants. Experimental approach: We prepared polyclonal antibodies by immunizing rabbits with the highly invasive 4T1 breast cancer cell line. Findings/Results: In vitro investigation indicated that the immunized rabbit serum inhibited cell proliferation and induced apoptosis in target tumor cells. Moreover, in vivo analysis showed enhanced anti-tumor efficacy of whole tumor cell lysate in combination with tumor cell-immunized serum. This combination therapy proved beneficial in significant inhibition of the tumor growth and the established tumor was entirely eradicated in treated mice. Conclusion and implications: Serial intravenous injections of tumor cell immunized rabbit serum significantly inhibited tumor cell proliferation and induced apoptosis in vitro and in vivo in combination with whole tumor lysate. This platform could be a promising method for developing clinical-grade vaccines and open up the possibility of addressing the effectiveness and safety of cancer vaccines.